In-vivo evidence of systemic endothelial vascular dysfunction in COVID-19. (15th December 2021) - Mejia-Renteria, Hernan; Travieso, Alejandro; Sagir, Adam; Martínez-Gómez, Eduardo; Carrascosa-Granada, Angela; Toya, Takumi; Núñez-Gil, Iván J.; Estrada, Vicente; Lerman, Amir; Escaned, Javier
Abstract: Background: Endothelial dysfunction is one of the underlying mechanisms to vascular and cardiac complications in patients with COVID-19. We sought to investigate the systemic vascular endothelial function and its temporal changes in COVID-19 patients from a non-invasive approach with reactive hyperemia peripheral arterial tonometry (PAT). Methods: This is a prospective, observational, case-control and blinded study. The population was comprised by 3 groups: patients investigated during acute COVID-19 (group 1), patients investigated during past COVID-19 (group 2), and controls 1:1 matched to COVID-19 patients by demographics and cardiovascular risk factors (group 3). The natural logarithmic scaled reactive hyperemia index (LnRHI), a measure of endothelium-mediated dilation of peripheral arteries, was obtained in all the participants and compared between study groups. Results: 144 participants were enrolled (72 COVID-19 patients and 72 matched controls). Median time from COVID-19 symptoms to PAT assessment was 9.5 and 101.5 days in groups 1 and 2, respectively. LnRHI was significantly lower in group 2 compared to both group 1 and controls (0.53 ± 0.23 group 2 vs. 0.72 ± 0.26 group 1, p = 0.0043; and 0.79 ± 0.23 in group 3, p < 0.0001). In addition, within group 1, it was observed a markedly decrease in LnRHI from acute COVID-19 to post infection stage (0.73 ± 0.23 vs. 0.42 ± 0.26, p = 0.0042). Conclusions: This study suggests a deleterious effect of SARS-CoV-2 infection on systemic vascular endothelial function. These findings open new venues to investigate the clinical implication and prognostic role of vascular endothelial dysfunction in COVID-19 patients and post-COVID syndrome using non-invasive techniques. Highlights: Endothelium-mediated vasodilator function is markedly reduced in COVID-19 post-infection stage compared to active infection and controls. These findings suggest that endothelial vascular dysfunction may be a chronic complication of the SARS-CoV-2 infection. This study opens new venues to investigate the clinical implication of vascular endothelial dysfunction in post-COVID syndrome using non-invasive techniques.